Sistem Pendukung Keputusan Pemilihan Kartu Internet Smartphone Menggunakan Metode MOORA dan WASPAS - Sulistya Kusuma Wardhani, Annisa Risqi; Yahya, Sitti Rachmawati; Tanwir, Tanwir; S, Usanto; Ahyuna, A (Building of Informatics, Technology and Science (BITS), 2023)
Currently the internet is the most widely used source of information among the public to find the information needed. The use of the internet can meet the needs of information sources that are fast, easy, precise, accurate and inexpensive. Through the internet can access a variety of information and knowledge according to relevant needs. The internet also has several advantages that are not shared by other conventional sources of information, access to information can be done with restrictions on distance, time and space which is part of the advantages of the internet. Making it possible to get the source of the information obtained. Thus, based on the results of a survey conducted by the previous author, involving 30 respondents who had used internet service packages before, the result was that 90% of respondents had difficulty making the right choice, according to the criteria they wanted. With a decision support system using the MOORA and WASPAS methods, it will be easier to find a solution to the problem of choosing an internet package based on the conditions offered by the various internet operators themselves. These criteria include speed, signal, internet quota, active period and price. Based on the calculations of these two methods, the best smartphone internet card title is alternative A1 with the name Telkomsel with a value for the MOORA method, which is 0.437, while the WASPAS method is 0.942 as the best alternative. So that people don't need to worry about choosing an internet card for smartphones that are good and have good access speeds